Shipping and the Environment - Andersson, Karin; Brynolf, Selma; Granhag, Lena; Lindgren, Fredrik (2021)
The sea provides the infrastructure for shipping, but it is also a very important part of the natural environment, providing many kinds of ecosystem services to man. More than 90% of international goods transport is performed by sea, and although shipping is the most energy efficient means of transport, it also causes impacts on nature, health, crops, and the built environment. The main part of emissions to air from shipping is related to the fuel. Traditionally, combustion engines using fossil heavy fuel oil (HFO) or diesel oil with emissions of sulfur, nitrogen oxides, particles, and other pollutants have been dominating. In order to decrease environmental impact, “zero emission” fuels and propulsion alternatives have been developed. The impact on the marine environment from, for example, oil spills and use of antifouling coatings on ships are other areas of concern. Shipping has a large challenge in becoming fossil-free and in developing “zero emission” technology in the coming decades.